Stereoselective Preparation and Reactions of Chiral Secondary Alkyllithiums - Skotnitzki, Juri; Kremsmair, Alexander; Knochel, Paul (Synthesis, 2020)
The preparation of chiral non-stabilized open-chain alkyllithium reagents prepared from the corresponding chiral secondary alkyl iodides and their subsequent transmetalation to the corresponding secondary alkylcopper or alkylzinc derivatives is reviewed. These new organometallic reagents allow the stereoselective preparation of a broad range of chiral molecules.1 Introduction2 Stereoselective Preparation of Secondary Alkyllithiums3 Preparation of Stereodefined Secondary Alkylcopper Reagents4 Preparation of Stereodefined Secondary Alkylzinc Derivatives and Their Stereoselective Cross-Coupling with Alkenyl and Aryl Halides5 Conclusion
Keywords: lithium; stereoselective; copper; zinc; cross-coupling; natural products